2020
DOI: 10.1155/2020/5494858
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Immune-Related Gene Prognostic Signature for Hepatocellular Carcinoma

Abstract: Immune-related genes (IRGs) have been identified as critical drivers of the initiation and progression of hepatocellular carcinoma (HCC). This study is aimed at constructing an IRG signature for HCC and validating its prognostic value in clinical application. The prognostic signature was developed by integrating multiple IRG expression data sets from TCGA and GEO databases. The IRGs were then combined with clinical features to validate the robustness of the prognostic signature through bioinformatics tools. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Yang et al revealed that a prediction immune model can forecast the survival outcome of cervical cancer ( 43 ). Chen et al reflected that a nine immune gene model has prognostic value for HCC ( 44 ). Nowadays, prognostic biomarkers related to tumor immunity in lung cancer are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al revealed that a prediction immune model can forecast the survival outcome of cervical cancer ( 43 ). Chen et al reflected that a nine immune gene model has prognostic value for HCC ( 44 ). Nowadays, prognostic biomarkers related to tumor immunity in lung cancer are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…GAST, PDGFA and STC1. Other studies on IRG signatures in human cancers include breast cancer [12], colorectal cancer [27], hepatocellular cancer [28], lung cancer [29], and gliomas [30]. Therefore, based on TCGA and microarray methods, IRG signatures for predicting the prognosis of patients have increasingly become the focus of research.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression levels were compared pairwise in a given sample or profile to compute a score for each RBP-related gene pair (RRGP). In a pairwise comparison, if the expression value of the first RBP gene was higher than that of the second one, the output score of this RRGP was 1; otherwise, the output was 0, according to the proposed method [15,22]. The advantage of analyzing genes in a pairwise comparison is without the requirement for standardization process for individualized analysis.…”
Section: Prognostic Signature Constructionmentioning
confidence: 99%
“…With the rapid development of sequencing and precision medicine, increasing evidence indicated that gene signatures at mRNA level had promising potential in predicting HCC prognosis. Numerous studies have proposed various signatures for survival prediction in patients with HCC [14][15][16][17][18][19]. For example, Liu et al [20] have established a novel six-gene signature for HCC prognosis prediction, but only one external validation cohort was used to validate the performance of the predicted model without comparison of its performance with other existed biomarkers.…”
Section: Introductionmentioning
confidence: 99%